MODERN INNOVATION PROCESS IN EDUCATION AND THE DEVELOPMENT OF NEW CONTENT AND ORGANIZATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article reveals the features of the modern innovation process in education in the Republics of Kazakhstan and Uzbekistan, the changes and developments taking place in the field of continuing education, the role of science in this process. The exchange of experience between universities of Kazakhstan and Uzbekistan is revealed. Among the most relevant is the transition of training to a credit-modular system.